2010
DOI: 10.1158/1078-0432.ccr-09-0816
|View full text |Cite
|
Sign up to set email alerts
|

NVP-BEZ235 as a New Therapeutic Option for Sarcomas

Abstract: NVP-BEZ235 displays the features to be considered for sarcoma therapy to potentiate the activity of other anticancer agents. The drug is currently undergoing phase I/II clinical trials in advanced cancer patients.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
141
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(153 citation statements)
references
References 31 publications
12
141
0
Order By: Relevance
“…NVP-BEZ235 is a pan-PI3K inhibitor that acts against all of the isoforms of PI3K and PI3K mutants. Previous studies have demonstrated the efficacy of NVP-BEZ235 as an antitumor agent in vitro and in vivo in glioblastoma, multiple myeloma, melanoma, lymphoma, www.nature.com/aps Pal I et al Acta Pharmacologica Sinica npg sarcoma, breast, lung, and ovarian cancer models [84][85][86][87][88][89][90][91][92][93] . In the case of colon cancer, NVP-BEZ23 decreases cellular proliferation and causes sustained inhibition of mTORC1 and mTORC2 with a transient PI3K blockade with no subsequent effect on apoptosis either in vitro or in vivo in a GEM model.…”
Section: Current Progress In Clinical Trialsmentioning
confidence: 99%
“…NVP-BEZ235 is a pan-PI3K inhibitor that acts against all of the isoforms of PI3K and PI3K mutants. Previous studies have demonstrated the efficacy of NVP-BEZ235 as an antitumor agent in vitro and in vivo in glioblastoma, multiple myeloma, melanoma, lymphoma, www.nature.com/aps Pal I et al Acta Pharmacologica Sinica npg sarcoma, breast, lung, and ovarian cancer models [84][85][86][87][88][89][90][91][92][93] . In the case of colon cancer, NVP-BEZ23 decreases cellular proliferation and causes sustained inhibition of mTORC1 and mTORC2 with a transient PI3K blockade with no subsequent effect on apoptosis either in vitro or in vivo in a GEM model.…”
Section: Current Progress In Clinical Trialsmentioning
confidence: 99%
“…The cell lines have been obtained as previously specified (Manara et al, 2010). Most of them have been authenticated recently (Ottaviano et al, 2010).…”
Section: Drugsmentioning
confidence: 99%
“…The ethical committee of the Rizzoli Institute approved the studies and informed consent was obtained from all subjects involved. To assess IGF-1R and IR expression, avidin-biotin-peroxidase procedure was used for immunostaining, as previously described (Manara et al, 2010). Sections were pretreated with a citrate buffer solution (0.01 mol/l citric acid and 0.01 mol/l sodium citrate (pH 6.0)) in a microwave oven at 750 W for three cycles of 5 min each to ensure antigen retrieval.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Previous data suggest that tyrosine kinase receptor signaling may play a role in the biology of more common pediatric solid tumors, such as medulloblastomas, ependymomas, and choroid plexus tumors, and in Ewing sarcomas and neuroblastomas. [9][10][11][12][13][14][15][16] Imatinib, a tyrosine kinase inhibitor directed against c-Abl, c-Kit and platelet-derived growth factor (PDGF) receptor subtypes a and b, 17 reportedly is tolerated relatively well in children. 18,19 Because it has been demonstrated that imatinib inhibits proliferation of the rhabdoid tumor cell line BT12, 20 our objective was to investigate the expression and functional role of tyrosine kinases targeted by imatinib in rhabdoid tumors.…”
mentioning
confidence: 99%